Contributions of the Joint Initiative for the Promotion of the One Health Approach in professional and community training to face the Covid-19 pandemic - Rachel, Creuza Rachel; Abou Mourad Ferreira, Mariana; de Oliveira Freitas, Natalia (Guará Journal, 2023)
The One Health approach integrates several professionals to solve problems involving human, animal, and environmental health, and its implementation is important for the prevention of pandemics, such as Covid-19. This experience report des-cribes how our extension project in One Health had a positive impact on the continuity of university activities during the Co-vid-19 pandemic and on the promotion of knowledge for the community in general. Due to social isolation, all activities were carried out virtually. The tasks, which started in August 2020, were: (i) webinars and meetings with professors, health professionals, and undergraduate and graduate students; (ii) international course involving professionals and students from Brazil, Germany, Mozambique, and Kosovo; and (iii) dissemi-nation of educational content in posts on social networks. We have done five webinars, 10 study groups to discuss current is-sues, more than 70 content on social media, and two editions of the international course on One Health. The project succeeded in uniting and training a range of professionals from different areas of activity, states, and countries, and in disseminating the One Health approach to the general population.